Holy Land Juices - Israa Odeh; Raghad Sabri (My University, 2023)
Nowadays, numerous companies are involved in beverage manufacturing, such as the National Beverage Company Coca-Cola/Cappy (NBC), and water bottling companies. These businesses rely on automating the filling and production processes to create a wide variety of drinks in substantial quantities with high precision. Manual methods of filling and capping, like those used by street drink vendors with carts, would demand significant time and effort, are susceptible to human labor errors, and the maximum production capacity per day would be insufficient to effectively meet customer demand. Additionally, they may not maintain the same level of quality and consistency because achieving precise proportions of juice and water manually each time is challenging. Therefore, automating this manual process by implementing an automated filling and capping machine is necessary. Our solution is to create an automatic juice filling and capping machine, comprising four key stages: detecting the size of the inserted bottle using three distinct IR Sensors in the initial stage, allowing only correctly sized Cappy bottles to proceed, while promptly rejecting others if they are oversized or undersized, ensuring a seamless process transition; then filling juice bottles with specific juice type and water concentrations in the following stage; conducting the capping process in the third stage; and finally, placing the capped bottles in designated boxes according to the filled juice type. The ultimate goal is to fully automate the juice filling and capping process, thereby reducing the reliance on manual labor. The Holy Land Juices project is developed using components such as the Arduino Mega, Arduino UNO, DC, servo, and stepper motors, liquid pumps, H-Bridge, YS-DIV268N driver, relays, ultrasonic sensors, IR sensors, laser diode, LDR light sensor module, and pneumatic pistons consisting of an air solenoid valve and an air cylinder.